MODEL OF TRAINING OF PRIMARY SCHOOL TEACHERS IN LEARNING THE BASICS OF INFORMATION AND COMMUNICATION TECHNOLOGIES (Journal of Information Technologies in Education (ITE), 2014)
In connection with the adoption of a new version of the state standard of primary education and the introduction of a primary school subject "Steps to a informatics" is particularly important problem of training of primary school teachers for training in accordance with the requirements of the standard. The model of training of primary school teachers in learning the basics of information and communication technologies was based on the analysis of the scientific literature and the results of international research on the training of future teachers and the formation of their information and communications expertise, practical experience in high school,. The model provides for the implementation of competence, personal and activity approaches, taking into account psychological and educational characteristics and the educational expectations of today's students, especially in terms of selection methods, forms and means of education. Organizational and pedagogical conditions of formation of readiness of primary school teachers in learning the basics of information and communication technologies were defined. Particular attention is given to the selection of the content of training students to use digital technologies in the educational process in primary school.Criteria and indicators by which the level of readiness assessment was conducted of primary school teachers in learning the basics of information and communication technologies are shown. The model was probed on the faculty of pre-school and primary education at the Kherson State University.
Keywords: model; the training of primary school teachers; expertise and information technology